The Integration Models of Character Education in Social Studies: A Literature Review - Dwi Ariyani, Yusinta; Wahyudi, Andi (Berpusi Publishing, 2023)
Current character education needs to be integrated into every lesson, including the integration of character education in social science. The ideas that should be prioritized in character education are values such as experience, empathy for others, personal obligation, feelings of the same destiny, suffering, peaceful conflict solvers. This study aimed to determine how to integrated character education in social science learning in elementary schools. The method used in this research is a literature study using book sources and articles, both national and international journals. The study focus is to reveal models that can be used to integrate character education in social science in elementary schools. The result is that character education can be integrated with the following four models: ARCS, VC, CTL, and LVE models. These models have in common is integrating values ​​through contextual problems. These contextual problems are the main components for the development of values ​​that are integrated into character education. However, the differences between the four models can be distinguished by the nature, context and application of social science learning. The integration of character education in every subject is essential for students' readiness to face every problem in their life. Further research needs to clarify the effectiveness of these models in efforts to develop character education.